Exploring the effect of pacing plan feedback for professional road cycling - Dukalski, R.; Lukosch, S.; Schwab, A.; Beek, P. J.; Brazier, F. M. (Proceedings, 2020)
In road cycling, cyclists strategically use their energetic resources in unique race-specific circumstances. For time-trial events, professional cycling teams design pacing plans aimed at the effective management of anaerobic work capacities of individual cyclists, allowing for more consistent speeds and therefore, faster times. Patently, adherence to such plans is essential. This paper reports on a field user-study on the effectiveness of providing a pacing plan to cyclists with the following information: (1) printed table alongside a display device with non-processed information (power, distance); and (2) aggregated, processed, just-in-time information on the same device (past, present, prospective; power, distance, W`). In both conditions, 15 road cyclists completed an 8 km open route mimicking race conditions, while adhering to pre-set pacing plans designed relative to their individual critical-power capabilities. Results indicated a linear load-to-adherence relationship and better adherence in condition (2). These findings will help guide future designs of adaptive feedback mechanisms for professional road cycling.